Association of SARS-CoV-2 infection with long-lasting increase in circulating IL-32 levels - Miano, Lorenzo; Sinopoli, Elena; Cherubini, Alessandro; Suffritti, Chiara; Pelusi, Serena; Rahmeh, Fatima; Lamorte, Giuseppe Enzo; Peyvandi, Flora; Blasi, Francesco; Grasselli, Giacomo; Bandera, Alessandra; Gualtierotti, Roberta; et al. (Frontiers in Immunology, 2026)
Background & aimsSevere Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection has a wide spectrum of clinical presentations ranging from asymptomatic viral replication to hyper-inflammatory syndrome and respiratory failure and can trigger immune disorders and long-COVID. Interleukin-32 (IL-32) is a pro-inflammatory cytokine induced during viral infections and chronic pulmonary disease.AimAim of this study was to investigate the impact of the SARS-CoV-2 pandemic and severe COVID-19 on circulating IL-32 levels.Study designObservational retrospective biomarker study.Patients & methodsWe analyzed 949 healthy blood donors (pre-pandemic and pandemic-era) and 212 patients hospitalized due to severe COVID-19 during the first five infection waves. IL-32 levels were measured by ELISA.ResultsPandemic-era blood plasma donors showed a +0.78 ± 0.09 log10 pg/ml mean increase in IL-32 (pandemic-era 2.91 ± 0.05 vs. pre-pandemic 2.14 ± 0.07 log10 pg/ml, p<0.0001). COVID-19 patients exhibited a similar elevated IL-32 compared to unexposed controls (+0.29 ± 0.11 log10 pg/ml, p=0.016; 2.43 ± 0.08 hospital admission vs. pre-pandemic). Among patients, mean IL-32 was higher in first-wave patients (2.68 ± 0.11 log10 pg/ml) than later waves (2.12 ± 0.11 log10 pg/ml). In setting of severe COVID-19, IL-32 levels were associated with corticosteroids administration (estimate1.99 ± 0.50; p<0.0001), whereas decreased during the later waves of infection (-0.56 ± 0.16; p=0.0005) and with age (estimate -0.01 ± 0.01; p=0.020). No links were found with sex, Intensive care unit admission, comorbidities, or mortality. A subset of the COVID patient cohort was tested for pro-inflammatory biomarkers: IL-32 displayed an inverse correlation with patients’ neutrophil-to-lymphocyte ratio (NLR) (estimate -0.23 ± 0.81; p=0.005) and not with IL-6 and biomarkers of endothelial dysfunction (n=42, p=NS). In patients with available follow-up (n=96), IL-32 remained stable up to one-year post-discharge (+0.03 ± 0.12 log10 pg/ml, p=0.970; 2.55 ± 0.15 hospital admission vs. follow-up 3–12 months 2.58 ± 0.15 log10 pg/ml).ConclusionsIL-32 levels increased following COVID-19, especially during the initial severe wave, and correlated with some markers of inflammation. IL-32 remained elevated up to one-year post-discharge, suggesting ongoing inflammation and supporting its potential as a biomarker for long-term sequelae.